(untitled) (Revista de Ciências Agroveterinárias, 2025)
Caffeine is an alkaloid that reduces perinatal hypoxia by acting on adenosine receptors in respiratory centres, enhancing respiratory capacity and piglet viability. This study aimed to evaluate the effects of acute subcutaneous caffeine administration during late gestation in multiparous sows on farrowing, pain behaviours, colostrum composition, and piglet behaviour during lactation. Sows were randomly assigned to two groups: control (NaCl 0.9%) or caffeine (0.5 g/sow/predicted piglet), with treatments given one day before farrowing. No significant effects were observed on farrowing duration, litter size, live or stillborn piglets, or painful behaviour. Although caffeine did not affect birth weight, piglets from the caffeine group gained 0.92 kg more (p<0.001) during weaning, likely due to higher protein concentrations in the colostrum. These findings suggest that a single low dose of caffeine late in gestation can improve neonatal vitality, colostrum quality, and weight gain without negatively affecting the farrowing process.